Public-Private Dynamics in Higher Education Expectations, Developments and Outcomes - Enders, Jürgen; Jongbloed, Ben (Science Studies, 2007)
Worldwide, scholarship and policy-making develop new ideas and models for the role of higher education and research in society and economy. This development points to changing relationships and boundaries between the public and private spheres in higher education including their public and private steering and funding, public-private partnerships between universities and firms, the rise of private higher education and of business models in the management of universities. The contributions to this edited volume investigate into the dynamics of blurring boundaries between the public and the private in higher education and their consequences for the university.